Aplikasi Pengelolaan Perlengkapan (SILAPAN) Berbasis Web pada PT. Telkom Witel Kalimantan Barat - Ismawan, Ismawan; Syamsiah, Nurfia Oktaviani (Jurnal Sistem Informasi Akuntansi, 2020)
PT. Telkom Witel Kalbar is an internet provider company for people with access to remote areas. In the new normal era is being found in the number of new customers causing access to equipment data required for installation more frequently. the more data that is input, it also has an effect on the amount of data that must be reported, so that if there is no system that can help this process, it is very possible that the reporting will take longer and its accuracy is guaranteed. The purpose of this research is to produce an equipment management application (SILAPAN) that can help solve problems. This study uses the waterfall method in building the system. Based on some literature and research results, this application can improve the effectiveness of business processes and the accuracy of reports and minimize the time for reporting